Processos temporais em Gérard Grisey - Santana, Charles de Paiva (2012)
After more than a quarter of century since the creation of ensemble L Itinéraire, the works created and the thought developed by its members remain as a highly fertile ground for musicological research and an essential reference for today's compositional practice. Among these composers, founders of the aesthetic trend so-called 'spectral', stands out Gérard Grisey (1946-1998) who left us a cohesive and preeminent work, admittedly one of the most influential of the past century s last decades. What we discern in his works is the concern with the thresholds of musical perception ( threshold in Latin is the origin of the term "liminal music" which he described his own music) and especially the notion of different musical 'temporalities'. Hence, we started from the conjecture that 'time' is the bedrock underlying the musical discourse used by the composer of Vortex Temporum. Aiming broader understanding of his music, without confining ourselves to the basic aspect of arithmetic operations on frequencies, we also examine the cardinal resources and ideas used by the French composer concerning the structure of instrumental timbre. This approach enabled us to distinguish how and which aspects of his language directed the development of many of his pieces, revealing, contiguously, the legitimate role played by time in his work. Thus, the core of this study presents the full formalization elaborated by Grisey regarding time and duration, anchored in the concepts of "skeleton", "flesh" and "skin of time." This formalization has led to considerations, albeit concise, about the influence of electronics, psychoacoustics and information theory. Likewise, in the light of the concepts elucidated during the research, we discuss Partiels, a key piece of the cycle Les Espaces Acoustiques and one of the pinnacles of contemporary repertoire.